Vulnerability effects of passengers' intermodal transfer distance preference and subway expansion on complementary urban public transportation systems. (February 2017) - Hong, Liu; Yan, Yongze; Ouyang, Min; Tian, Hui; He, Xiaozheng
Abstract: The vulnerability studies on urban public transportation systems have attracted growing attentions in recent years, due to their important role in the economy development of a city and the well-beings of its citizens. This paper proposes a vulnerability model of complementary urban public transportation systems (CUPTSs) composed of bus systems and subway systems, with the consideration of passengers' intermodal transfer distance preference ( PITDP ) to capture different levels of complementary strength between the two systems. Based on the model, this paper further introduces a CUPTSs-aimed vulnerability analysis method from two specific aspects: (a) vulnerability effects of different PITDP values, which facilitate the design of policies to change PITDP to reduce system vulnerability; (b) vulnerability effects of different subway expansion plans, which facilitate the vulnerability investigation of current expansion plan and the identification of the optimal expansion plan from the system vulnerability perspective. The proposed CUPTSs-aimed vulnerability analysis method is applied to investigate the complementary bus and subway systems in the city of Wuhan, China. The insights from this study are helpful to analyze other CUPTSs for valuable planning suggestions from the vulnerability perspective. Highlights: We model complementary urban public transportation systems' (CUPTSs) vulnerability. We use a PITDP metric to capture different levels of complementary relationship. We study vulnerability under different PITDP and different subway expansion plans. We analyze dynamic vulnerability of CUPTSs during their expansion process.